2017
DOI: 10.1007/s13691-017-0311-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful conversion surgery for unresectable pancreatic cancer with peritoneal metastases after neoadjuvant albumin-bound paclitaxel and gemcitabine chemotherapy: case report and literature review

Abstract: We report a case in which combination therapy with albumin-bound paclitaxel (nab-paclitaxel) and gemcitabine converted unresectable pancreatic cancer with peritoneal metastases into resectable disease. The patient was a 71-year-old woman with anorexia. Enhanced abdominal computed tomography (CT) showed an atrophic pancreatic body and tail, dilated main pancreatic duct, peritoneal dissemination, portal vein stricture, bile duct stricture and wall thickening, and blockage of the right ureter. She was diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The results demonstrated that neoadjuvant FOLFIRINOX significantly improved overall survival over that with GA after adjusting for potential confounding factors. A lot of case reports also separately showed the successful conversion cases by neoadjuvant GA or FOLFIRINOX (34)(35)(36)(37)(38)(39)(40). For example, Gostimir et al presented a case whose lesion had decreased in size and complete pathological response after underwent treatment with a total of 13 cycles of FOLFIRINOX.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that neoadjuvant FOLFIRINOX significantly improved overall survival over that with GA after adjusting for potential confounding factors. A lot of case reports also separately showed the successful conversion cases by neoadjuvant GA or FOLFIRINOX (34)(35)(36)(37)(38)(39)(40). For example, Gostimir et al presented a case whose lesion had decreased in size and complete pathological response after underwent treatment with a total of 13 cycles of FOLFIRINOX.…”
Section: Discussionmentioning
confidence: 99%